Larangan Menikahi Kerabat Mantan Istri Sesuku dalam Adat Masyarakat Nagari Koto Lamo, Kecamatan Kapur IX Perspektif Urf - Reti Alia Putri; Helfi Helfi (AHKAM, 2026)
The prohibition against marrying relatives of a former wife from the same clan in Minangkabau society is a customary practice related to the regulation of kinship relations, social harmony, and compliance with clan norms. Although this theme has been examined in several previous studies, research specifically discussing the prohibition against marrying relatives of a former wife from the same clan in the customs of the Nagari Koto Lamo community, Kapur IX Subdistrict, from the perspective of ‘urf remains limited. This study aims to analyze the implementation of the prohibition against marrying relatives of a former wife from the same clan in the customs of the Nagari Koto Lamo community and to examine it from the perspective of ‘urf in Islamic law. This study used a qualitative approach with a field research design. The research informants consisted of niniak mamak, alim ulama, community leaders, and members of the Nagari Koto Lamo community who were selected purposively. Data were collected through structured interviews and documentation, and were then analyzed descriptively and inductively. The results showed that the Nagari Koto Lamo community prohibits a person from marrying relatives of a former wife who come from the same clan or the same soko because it is considered likely to cause social conflict, damage kinship relations, and disrupt clan harmony. Violation of this prohibition is subject to a customary sanction in the form of being banished according to custom. From the perspective of ‘urf, this prohibition is classified as ‘urf fasid because it contradicts the provisions of Islamic law, which does not prohibit such a marriage as long as there is no mahram relationship. These findings contribute to the development of studies on Islamic family law, customary law, and ushul fiqh, particularly in understanding the relationship between custom and Islamic law in Minangkabau society.